Hubungan antara Promosi dengan Pengambilan Keputusan Peserta Didik untuk Mengikuti Bimbingan Belajar di BBC - Suci Junianti; Jamaris Jamaris; Vevi Sunarti (Universitas Negeri Padang, 2018)
This study aims to see whether there is a relationship between promotion and decision making learners in following the tutoring in BBC Limbanang Kecamatan Suliki Kabupaten Lima Puluh Kota. This type of research is correlational. The population in this study is the citizens learn BBC learning guidance. Sampling technique in this research is stratified random sampling from entire population. Data collection techniques used are questionnaires, while the data collection tool questionnaire. Technique of data analysis by using formula of percentage and product moment. From the results of the study showed that: promotion done by the guidance of learning in BBC less good so that decision to follow guidance study in BBC considered less good also by learners.